2018
DOI: 10.1002/app.47409
|View full text |Cite
|
Sign up to set email alerts
|

Remarkable change in the broadband electrical behavior of poly(vinylidene fluoride)–multiwalled carbon nanotube nanocomposites with the use of different processing routes

Abstract: Poly(vinylidene fluoride) (PVDF) nanocomposites have plenty of applications in the electronic realm. In this study, we produced nanocomposites based on PVDF and multiwalled carbon nanotubes (MWCNTs), with various MWCNT loadings, using three different processing routes: solution mixing, melt mixing, and electrospinning. The broadband electrical behavior of these nanocomposites was studied and compared via impedance spectroscopy. The morphologies of the nanocomposites were characterized by transmission electron … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 55 publications
(73 reference statements)
2
13
0
Order By: Relevance
“…The sample of neat PVDF had a single melting peak, where melting temperature (T m ) 170 C, which was ascribed to the melting of α phase crystals. 1 The same behavior was observed for PVDF-el, PVDF/MWCNT and PVDF/MWCNT-el. T m was 170 C for all these samples.…”
Section: Rheological Oscillatory Measurementssupporting
confidence: 64%
See 2 more Smart Citations
“…The sample of neat PVDF had a single melting peak, where melting temperature (T m ) 170 C, which was ascribed to the melting of α phase crystals. 1 The same behavior was observed for PVDF-el, PVDF/MWCNT and PVDF/MWCNT-el. T m was 170 C for all these samples.…”
Section: Rheological Oscillatory Measurementssupporting
confidence: 64%
“…It is known that structure and properties of PVDF nanocomposites can be dramatically changed under different processing approaches or flow fields. In a previous work, 27 we showed that electrical properties of PVDF/ MWCNT nanocomposites were completely different depending upon the processing method used. While melt and solution mixing led to the dispersion of MWCNT through the whole PVDF matrix yielding conductive nanocomposites, the process of electrospinning promoted high degrees of MWCNT alignment through the PVDF yielding highly insulators nanocomposites.…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…The following MWCNT concentrations were used for this study: 0.1, 1.0, 3.0 and 5.0 vol.% MWCNT. These filler loadings were selected based on previous works [1,20,21] , which pointed out a value of 0.31vol.% MWCNT for the theoretical percolation threshold of a generic polymer matrix filled with the MWCNT NC7000 from Nanocyl [1,3,22] . After melt mixing, films of the resulting nanocomposites were produced by compression molding at 190ºC under 8 MPa of pressure using a hot press.…”
Section: Melt Mixingmentioning
confidence: 99%
“…The use of multiwall carbon nanotubes (MWCNT) in polymeric matrixes to produce conductive nanocomposites has been widely studied [1,2] . Among the broad range of polymer matrixes, the thermoplastic elastomers have the advantage of behaving as elastomers at room temperature, but being able to be processed as thermoplastics [3] .…”
Section: Introductionmentioning
confidence: 99%